Exploring The Technological Pedagogical and Content Knowledge (TPACK) of Driving Teacher (Guru Penggerak) In Banyuwangi, Indonesia - Faisol, Aninditya Messaurina; Susanti, Laily Yunita (Proceeding International Conference on Education, 2025)
Teachers play a crucial role in the success of education, particularly within Indonesia's Merdeka Curriculum, which introduces the concept of Guru Penggerak (Driving Teacher). These teachers are positioned as agents of change, expected to integrate technology, pedagogy, and content through the Technological Pedagogical and Content Knowledge (TPACK) framework, especially in science education. This study aims to describe the TPACK profiles of junior high school science driving teacher in Banyuwangi Regency and identify both supporting and inhibiting factors. A descriptive qualitative approach was applied, with data collected through interviews, questionnaires, classroom observations, and document analysis. Data were analyzed using data reduction, presentation, and conclusion drawing, and validated through source and method triangulation. The results show that: (1) TPACK profiles based on CoRe + Technology are generally strong, as teachers demonstrate an understanding of the big ideas and key concepts in the material, which they record in CoRe and Technology sheets used as a foundation for developing students’ conceptual understanding; (2) Observations and PaP-eRs indicate that: a) TK includes digital literacy skills; b) PK includes classroom management with ice-breaking, planning with teaching modules, phased implementation (introduction, core, closing), assessment via literacy, numeracy, and projects, and evaluation through peer learning groups; and c) CK includes using science textbooks as primary resources and providing examples relevant to the theory; and (3) Supporting factors include adequate access to technology, facilities, and peer collaboration, while inhibiting factors involve limited knowledge of TPACK integration and insufficient time for lesson preparation.